Analysis of Genetic Variability, Heritability and Genetic Advance for Yield and Yield Related Traits in Chilli (Capsicum annuum L.) - Saisupriya, Pallerla; Saidaiah, P.; Pandravada, S. R. (International Journal of Bio-resource and Stress Management, 2022)
Thirty five chilli genotypes were evaluated in a randomized block design at College of Horticulture, Rajendranagar, Sri Konda Laxman Telangana State Horticultural University, Hyderabad, Telangana state, India during Kharif, 2019 for seven months and at National Bureau of Plant Genetic Resources, Regional station, Rajendranagar, Hyderabad during Rabi 2019-20 for seven months to estimate genetic variability, heritability, genetic advance and genetic advance as % of mean of seventeen yield and yield related traits. For all the traits studied, the magnitude of PCV was higher than corresponding GCV. High Phenotypic coefficient of variation and genotypic coefficient of variation estimates were recorded for plant height, plant spread, fruit length, fruit diameter, number of fruits plant-1, fruit weight, fruit yield plant-1, fruit yield plot-1, ascorbic acid, capsaicin content and capsanthin content indicating the existence of wider genetic variability for these traits in the genotypes studied. High heritability was recorded for the traits Days to first flowering, Fruit length, Fruit diameter, No. of fruits plant-1, Fruit weight, Fruit yield plant-1, Fruit yield plot-1, Ascorbic acid, Chlorophyll content, Capsaicin content and Capsanthin content. High heritability coupled with high genetic advance as % mean indicates existence of additive gene action which was observed in fruit length, fruit diameter, number of fruits plant-1, fruit weight, fruit yield plant-1, fruit yield plot-1, ascorbic acid, chlorophyll content, capsaicin content and capsanthin content. Hence these traits can be improved by direct selection.